(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article is considered the usage and typology of interjection in Kazakh, Russian and English languages. Their similarities and difference are determined by giving concrete examples. From the examples offer national and cultural peculiarities of interjections Kazakh, Russian and English languages. Conclusions are based on the results of comparative analysis of the examples. Interjections are words used for the sole purpose of expressing emotion. The history of studying of interjections shows that, the treatment of an interjection is one of the most disputable and at the same time the least studied areas of science about language in foreign, and in the Kazakh and Russian linguistics. But researches were devoted to the comparative analysis of interjections of different languages (private languages), such as, Russian and English, German, French, etc. And research of comparative analysis of the Kazakh, English and Russian interjections is carried out for the first time. That fact that complex studying of onomatopoeias in the comparative plan so far wasn’t carried out caused a choice of a subject of this work. A comparison between English and Arabic interjections is conducted in an attempt to find out whether equivalents can be found in both languages .